2020
DOI: 10.1002/job.2447
|View full text |Cite
|
Sign up to set email alerts
|

How certain can we really be that our boss is trustworthy, and does it matter? A metacognitive perspective on employee evaluations of supervisor trustworthiness

Abstract: Summary This research helps to integrate the metacognitive concept of evaluation certainty into the trust literature by demonstrating that certainty can amplify the effects of trustworthiness evaluations and stabilize trustworthiness evaluations over time. Across an experimental study (Study 1) and a multiwave survey of employees (Study 2), we show that trustworthiness evaluations exert a stronger influence on individuals' trust at higher levels of certainty and that trust transmits the multiplicative effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…These results are consistent with the basic ideology of authentic leadership and trust development as put forth by Avolio et al (2004). Since Holtz et al (2020), suggest that trust is a process of risk-taking and making oneself vulnerable to someone's actions, the context of performance appraisal can be a typical example of such vulnerable scenarios where the ratee relies upon the rater and a trusting relationship is likely to reduce ratees' anxiety and uncertainty about the outcomes, which is manifested in the resulting perception of accuracy utility of feedback received. The substantiation of hypotheses suggests that authentic leadership brings favourable feedback reactions in the performance appraisal context.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are consistent with the basic ideology of authentic leadership and trust development as put forth by Avolio et al (2004). Since Holtz et al (2020), suggest that trust is a process of risk-taking and making oneself vulnerable to someone's actions, the context of performance appraisal can be a typical example of such vulnerable scenarios where the ratee relies upon the rater and a trusting relationship is likely to reduce ratees' anxiety and uncertainty about the outcomes, which is manifested in the resulting perception of accuracy utility of feedback received. The substantiation of hypotheses suggests that authentic leadership brings favourable feedback reactions in the performance appraisal context.…”
Section: Discussionsupporting
confidence: 88%
“…In their study, Holtz et al (2020) presented trust as risk-taking and making oneself vulnerable to the actions of someone else when he or she cannot be restricted or monitored. Performance appraisal situation has a unique relevance with this vulnerability because the employees whose performance is evaluated may look at the situation as a risky one and their feedback reactions are expected to be affected by trust levels they have developed with their manager (Mulvaney, 2019).…”
Section: Review Of Literature and Hypothesis Developmentmentioning
confidence: 99%
“…They found that follower risk aversion mediates the positive link between self-sacrificial leadership and followers taking charge. Holz et al. (2020) again found that follower risk-taking propensities are a by-product of their certainty about their trustworthiness evaluations of their superiors.…”
Section: Leadership and Risk In Management Studies Researchmentioning
confidence: 94%
“…Building on the work of Mayer et al (1995), recent studies have confirmed that trust cannot be maintained or developed when the levels of superior's competence (ability) and fairness (integrity) are low (Poon, 2013;Bugdol, 2018), or the organizational culture does not support it (Jabeen & Isakovic, 2018;Jeong & Chun, 2019). Furthermore, the level of inferior managers' certainty in their subjective trustworthiness evaluation is an additional variable that has to be considered (Holtz et al, 2020). Under the diverse influence of suchlike factors, superior managers are trusted to different degrees (Andersen, 2019).…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%